Chased by a Unicorn - Georgios Orfanidis (Medievalista)
The parable of the Futile Life, which is an excerpt of the medieval, multilingual novel Barlaam and Josaphat, conceals a unique interpretative approach, in terms of symbolism, of an ancient and intercultural mythological symbol, that of the unicorn. From a first examination of the cultural environment – textual and iconographical – of the unicorn’s appearance, it would seem that the symbolic substance of this animal motif was imbued with the notions of the high virtues of the Christian ideological system (e.g. virginity, purity, salvation). However, the parabolic narrative of the Futile Life reveals another aspect. This is the aspect of the inward cruel power that drives a man to the wrong choice, preventing him from finding the proper spiritual way out to save himself after his physical death in the vanity world in which he lives transiently. Probably, the beauty of a unicorn now symbolizes something not so pure. Indeed, the story of the Futile Life is transformed into one of the most common iconographic themes in monumental Christian painting, and, at the same time, it raises reasonable concerns while seeking adequate explanations. So, through a list of relevant examples of monumental and miniature art, we will look for the beginnings of the two aspects of this ancient symbol, with an emphasis on the parable under examination, offering a new perspective on the semiotic analysis of Antiquity during the Middle Ages.